(untitled) (Journal of Parents and Teachers, 2014)
This article deals with the problems and difficulties that make teaching a risky profession to suffer from stress. Numerous studies show that teaching is closely related to stress. This article explains many causes that are relates to stress from teaching, one example being the ongoing educational reforms. In addition, the responsibility for training individuals falls on the teacher’s shoulders. The role of the teacher is subject to total instability, especially because of the expectations that different groups of people transmit. Stress can generate work tension, dissatisfaction and low levels of self-confidence. At the end of the article several strategies are given to face stress, an example is cognitive restructuring or relaxation.